1997
DOI: 10.1038/sj.bmt.1700833
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral stem cell mobilization and engraftment in patients over age 60

Abstract: Data from 225 multiple myeloma (MM) patients, undergoing peripheral stem cell (PBSC) mobilization with high-dose cyclophosphamide and hematopoietic growth factors, were analyzed for median CD34+ cell count and median time to post-transplant neutrophil (ANC > 500/microliters) and platelet (> 50,000/microliters) recovery according to age groups (20-49, 50-59 and > or = 60 years) and duration of prior therapy (< or = 12, 13-24, or > 24 months). Fifty-seven of the 225 patients were > or = 60 years. No difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…No significant differences were observed in the success rate or complications associated with progenitor cell mobilization with CY plus G-CSF according to age, nor were there any differences in the time to engraftment. These observations are in line with the study of Guba et al, 15 who observed no differences in the number of CD34-positive cells collected or in the time to engraftment in myeloma patients according to the age.…”
Section: Discussionsupporting
confidence: 82%
“…No significant differences were observed in the success rate or complications associated with progenitor cell mobilization with CY plus G-CSF according to age, nor were there any differences in the time to engraftment. These observations are in line with the study of Guba et al, 15 who observed no differences in the number of CD34-positive cells collected or in the time to engraftment in myeloma patients according to the age.…”
Section: Discussionsupporting
confidence: 82%
“…Transplant-related non-hematological toxicity was surprisingly not excessive in our elderly patients although one would perhaps expect a higher incidence due to more compromised organ function in this older population. 16 In our study the findings that multiple cycles of standard-dose chemotherapy may be connected with worse outcome of HDC, 12,17 were not confirmed. The clinical outcome of patients receiving more or less intensive first-line therapy was similar.…”
Section: Discussioncontrasting
confidence: 41%
“…Stem cell collection and intensification were performed as in younger patients, as has been previously reported. 21 However, the freedom from progression was significantly shorter than in younger patients. We observed a trend (P = 0.09) towards a more prolonged OS in younger patients.…”
mentioning
confidence: 95%